X-ray magnetic circular dichroism in d and f ferromagnetic materials: recent theoretical progress. Part II (Review Article): - Antonov, V.N.; Shpak, A.P.; Yaresko, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The current status of theoretical understanding of the x-ray magnetic circular dichroism (XMCD) of 4 fand 5 f compounds is reviewed. Energy band theory based upon the local spin-density approximation (LSDA) describes the XMCD spectra of transition metal compounds with high accuracy. However, the LSDA does not suffice for lanthanide compounds which have a correlated 4 f shell. A satisfactory description of the XMCD spectra could be obtained by using a generalization of the LSDA, in which explicitly f electron Coulomb correlation are taken into account (LSDA + U approach). As examples of this group we consider GdN compound. We also consider uranium 5 f compounds. In those compounds where the 5 f electrons are rather delocalized, the LSDA describes the XMCD spectra reasonably well. As example of this group we consider UFe2. Particular differences occur for the uranium compounds where the 5 f electrons are neither delocalized nor localized, but more or less semilocalized. Typical examples are UXAl (X = Co, Rh, and Pt), and UX (X = S, Se, Te). The semilocalized 5 f 's are, however, not inert, but their interaction with conduction electrons plays an important role. We also consider the electronic structure and XMCD spectra of heavy-fermion compounds UPt3, URu2Si2, UPd2Al3, UNi2Al3, and UBe13 where the degree of the 5 f localization is increased in comparison with other uranium compounds. The electronic structure and XMCD spectra of UGe2 which possesses simultaneously ferromagnetism and superconductivity also presented. Recently achieved improvements for describing 5 f compounds are discussed.